Mapping Evidence on the Effectiveness of Health Education Based on Health Belief Model (HBM) for Promoting Self-Care Behavior in Patients with Type 2 Diabetes Mellitus: A Scoping Review - Wa Ode Umi Kalsum; Sri Mulyani; Uki Noviana; Fahrunnissa Tehepelasury; Rurry Nindya Taluphyta (Universitas Airlangga, 2026)
Introduction: Type 2 diabetes mellitus is one of the noncommunicable diseases with a high prevalence worldwide. Self-care has been shown to play a crucial role in controlling blood glucose levels and preventing complications. Various studies show that patient self-care levels remain low and are often influenced by inappropriate health beliefs. This scoping review aims to map and synthesize the available evidence on the effectiveness of health education based on HBM for promoting self-care behaviour in patients with type 2 diabetes mellitus. Methods: This study used a scoping review design based on Arksey and O’Malley’s guidelines. Searches were conducted in Scopus, ScienceDirect, PubMed, ProQuest, and a manual search in Google Scholar using the PICO approach. Eligible studies were English full-text articles published from 2020 to 2025 and designed as RCTs or quasi-experimental studies. Critical appraisal was performed using JBI tools. Results: Six articles from India, Iran, Egypt, and China were included. Educational interventions based on HBM utilized various media (booklets, videos, pamphlets, telemedicine) and methods (lectures, discussions, demonstrations, peer groups, family involvement) with a duration of 3–8 sessions and follow-up periods of 1–6 months. All studies reported improvements in self-care behavior and HBM components (perceived susceptibility, severity, benefits, barriers, cues to action, self-efficacy). Two studies noted a significant decrease in HbA1c, one study reported an improvement in quality of life, and two studies reported an increase in knowledge. Conclusion: This scoping review indicates that educational interventions based on the HBM are consistently associated with improvement in self-care behavior and HBM components among patients with type 2 diabetes mellitus, with some studies also reporting reductions in HbA1c, improved knowledge, and better quality of life. Further rigorous studies and formal evidence synthesis are needed before health education based on HBM can be recommended as a standard strategy in diabetes self-care.